Ornithological and ecological studies in S. W. Greenland (59°46’-62°27’ N. Lat.) - Salomonsen, Finn (Meddelelser om Grønland, 1979)
This work is the first in a series of papers describing the ecology of birds in Western Greenland, particularly the sea-birds. In this paper the situation in S. W. Greenland has been described, including the districts of Nanortalik, Julianehab, Narssaq and Frederikshab. In the former three districts, which constitute the southernmost part of West Greenland, the East Greenland ice ("Storis") virtually prevents the formation of actual sea-bird colonies. On the other hand, the southern position of this area has given rise to the development of a more mitigated climate in the interior country and this has caused the formation of a subarctic zone, being part of the boreal, not the arctic biome. The climate, the plan-cover and other particulars of the subarctic zone are described, including the human trades in this zone as consequences of the climate. A detailed account of the immigration of six subarctic bird-species to Greenland is given as well as notes on their distribution and life-habits in Greenland. In Frederikshab District a number of sea-bird colonies have been developed, some of which are rather large. The natural history of these colonies are described in detail, and a methodical analysis is given of the factors governing their development, as well as the significant botanical consequences of the presence of avian guano, important even for the human population. Some new designations for various conceptions have been proposed, necessary for the discussion of these matters which have not previously been seriously studied. A description of each sea-bird colony in Frederikshåb District is followed by notes on the sea-bird migration and on local bird-names in the district and, finally, by a discussion on the transglacial migration.